A new species of Calyculogygas (Malvaceae) from southern Brazil - Grings, Martin; Boldrini, Ilsi Iob; Knob, Alberto; Bordignon, Sérgio Augusto De Loreto (Phytotaxa, 2014)
Calyculogyas serrana (Malvaceae), a new species endemic to the highland slopes of “Serra Geral” plateau, in the Brazilian state of Rio Grande do Sul, is described and illustrated and we also provide information regarding its habitat and conservation status. The genus Calyculogygas has now two species, of which Calyculogygas uruguayensis is the type species. The two species are differentiated with a key, a table and illustrations, and we also provide a map of their distributions.